Self-Reevaluation and Anticipated Regret Did Not Change Attitude, Nor Perceived Distance in an Online Context - Crutzen, Rik; Cyr, Dianne; Taylor, Sarah E.; Lim, Eric; Ruiter, Robert A. C. (Frontiers in Psychology, 2017)
Internet-delivered interventions can be effective in changing behaviour, but more research is needed on effective elements of behaviour change interventions. Moreover, although anonymity is one of the advantages of using an online context, it might also increase the perceived distance between the participant and the intervention. Hence, the current study investigated whether the behaviour change methods of self-reevaluation and anticipated regret can be used to narrow the perceived distance and, ultimately, foster attitude change. A 3x3 factorial between-persons design with an additional control group was used (N=466), resulting in a total of 10 conditions (n’s ranging from 43-49). The first factor manipulated is assessment of self-image; cognitive, affective, or the combination of both. The second factor manipulated is behavioural focus; self-image with behaviour, without behaviour or both with and without behaviour. Post-test measurements were conducted immediately after the manipulation. The key finding of the current study is that the behaviour change methods of self-reevaluation and anticipated regret did not have an impact on changes in attitude towards oral contraceptive use, nor on the distance perceived by participants. Despite the null results, the current study contributes to the body of evidence regarding self-reevaluation and anticipated regret, which can be integrated in meta-regressions of experimental studies to advance behaviour change theory.